Fourier Splitting Method for Kawahara Type Equations. (26th August 2014) - Suárez, Pablo U.; Morales, J. Héctor
Abstract : In this work, we integrate numerically the Kawahara and generalized Kawahara equation by using an algorithm based on Strang's splitting method. The linear part is solved using the Fourier transform and the nonlinear part is solved with the aid of the exponential operator method. To assess the accuracy of the solution, we compare known analytical solutions with the numerical solution. Further, we show that as t increases the conserved quantities remain constant.